LKPD Interaktif Berbasis Discovery Learning: Inovasi Media Pembelajaran dalam Meningkatkan Penalaran Matematis - Fungky Marian; Ruri Handayani; Izza Eka Ningrum (Indiktika : Jurnal Inovasi Pendidikan Matematika, 2026)
This study aims to analyze the effectiveness of an interactive Student Worksheet (LKPD) based on Discovery Learning in enhancing students’ mathematical reasoning skills on the topic of sets. A quasi-experimental design with a one-group pretest–posttest approach was employed, involving 30 seventh-grade students from SMPN 2 Banguntapan, Yogyakarta. Data were collected through validated mathematical reasoning tests and supplemented by expert validation conducted by two content experts and two media experts to ensure the LKPD’s quality in terms of content, language, and interactive design. Results showed a substantial improvement in students’ performance, with the mean score increasing from 59.3 (pretest) to 84.7 (posttest), representing a 42.8% gain. A paired t-test confirmed a statistically significant difference between the two scores (Sig. (2-tailed) = 0.000 < 0.05). These findings indicate that the interactive LKPD grounded in Discovery Learning effectively enhances mathematical reasoning. Given its structured yet student-centered approach, this learning tool holds strong potential for broader implementation across diverse classroom settings in Indonesia and similar educational contexts.